Characteristics and Mutational Hotspots of Plastomes in Debregeasia (Urticaceae) - Wang, Ruo-Nan; Milne, Richard I.; Du, Xin-Yu; Liu, Jie; Wu, Zeng-Yuan (Frontiers in Genetics, 2020)
Debregeasia is an economically important genus of the nettle family (Urticaceae). Previous systematic studies based on morphology, or using up to four plastome regions, have not satisfactorily resolved relationships within the genus. Here, we report 25 new plastomes for Urticaceae, including 12 plastomes from five Debregeasia species and 13 plastomes from other genera. Together with the one published plastome for Debregeasia, we analyzed plastome structure and character, identified mutation hotspots and loci under selection, and constructed phylogenies. The plastomes of Debregeasia were found to be very conservative, with a size from 155,743 bp to 156,065 bp, and no structural variation. Eleven mutation hotspots were identified, including three (rpoB-trnC-GCA, trnT-GGU-psbD and ycf1) that are highly variable both within Debregeasia and among genera; these show high potential value for future DNA barcoding, population genetics and phylogenetic reconstruction. Selection pressure analysis revealed nine genes (clpP, ndhF, petB, psbA, psbK, rbcL, rpl23, ycf2 and ycf1) that may experience positive selection. Phylogenomic analyses results suggest that Debregeasia was monophyletic, and closest to Boehmeria among genera examined. Within Debregeasia, D. longifolia was sister to D. saeneb, whereas D. elliptica, D. orientalis with D. squamata formed the other subclade. This study enriches genetic resources for Urticaceae, and highlights the utility of plastome data for detecting mutation hotspots for evolutionary and systematic analysis.